MODEL PEMILIHAN MODA ATAS PELAYANAN MONOREL JAKARTA BERDASARKAN DATA STATED PREFERENCE (SP) - Sjafruddin, Ade; Haryoyudanto, Apriadi; Wirahadikusumah, Reini D.; Amalia, Nina (Jurnal Transportasi, 2008)
AbstractÂ The need for mass transportation urges the government of Jakarta to build a monorail system. Monorail will increase the capacity ofÂ  public transportation system and give a new color to the urban transportation services. Users will have an additional mode choice and then make their preferences. Userâs behaviour when choosing mode can be modeled using Stated Preference data. By using Stated Preference, monorail can be compared objectively to existing modes, namely private car, AC bus, non-AC bus, and busway using specific service attributes. Attributes used in this study are journey time, fare, frequency of departure, delay, and walking time to station. Stated Preference data were obtained from a survey to prospective passengers in the service area of the Green Line monorail corridor. Binary logit models were employed to model mode choices and the utility function was in a linear form. Calibration was done by multiple linear regression. Four mode choice models were then obtained, namely monorail versus private car model, monorail versus AC bus model, monorail versus non-AC bus model and monorail versus busway model.Â Keywords:Â  monorail, mode choice, service attribute, Stated Preference (SP)Â